ANALISIS KETERKAITAN SOSIOKULTURAL SUBAK DENGAN EFISIENSI USAHATANI PADI SAWAH SISTEM TAPIN DAN TABELA (STUDI KASUS SUBAK LINGGA MERTA KABUPATEN KOLAKA) - Nyoman Darsana; Ayub M. Padangaran; Muhammad Arief Dirgantoro (Jurnal Sosio Agribisnis, 2018)
The aims of this study were: to describe farm rice cultivation with tapin and tabela systems practiced by subak and non-subak farmers; to find out the efficiency of farm rice cultivation with tapin and tabela systems on subak and non-subak farmers; to establish the relationship between socio-cultural subak and the efficiency of farm rice cultivation. The study was conducted from June to December 2016. Objects of the study were subak and non-subak farmers who adopted tapin and tabela systems. Data were collected using observation, interview, and study of literature. A total of 60 samples/respondents which were determined purposively and randomly. A descriptive statistical analysis and R/C ratio analysis were used to analyze data. Results of the study showed that: farm rice cultivation by subak farmers who adopted tapin and tabela system was different from that of non-subak farmers, particularly in social and religious aspects; the productivity and efficiency value of subak farmers was higher than that of non-subak farmers, with the subak farmers using tapin and tabela system gained a total of productivity value of Rp 20.741.945,-/hectare and those adopting tabela system reached Rp 20.493.410,-/hectare, and the efficiency value of tapin and tabela was 2.23 and 2.56 respectively. The productivity value of non-subak farmers was lower, with Rp 15.972.705,-/hectare and Rp 15.050.000,-/hectare gained by tapin system and tabela system respectively; it was found from a cross table analysis that the mean score of technology applied by subak farmers per respondent was higher than that of non-subak farmers, which was 12: 9.5 in the tapin system, and 11.27:9 in the tabela system. Based on the score of technology and R/C values, it could be established that there was no relationship between R/C both subak and non-subak.  Keywords: socio-cultural; subak; tapin, tabela; productivity; efficiency.